Assessing brushite-polyphosphate nanocomposites as nanofertilizers for improved phosphorus use efficiency in maize - Houssameddine Mansouri; Bouthayna El Amine; Hamid Ait Said; Hassan Noukrati; François Perreault; Abdallah Oukarroum; Hicham Ben Youcef (Journal of Agriculture and Food Research, 2025)
Phosphorus (P) inefficiency in conventional fertilizers poses a critical challenge to sustainable agriculture and global food security. This study introduces brushite-polyphosphate (DCPD-PolyP) nanofertilizers as a novel, high-efficiency alternative to enhance phosphorus availability, micronutrient uptake, and maize productivity. Advanced characterization using X-ray diffraction and scanning electron microscopy confirmed the amorphous nanostructure of brushite-polyphosphate (50–100 nm), while inductively coupled plasma optical emission spectroscopy revealed high phosphorus (22.72 %) and reduced calcium (18.66 %) content in the composite. In greenhouse trials, maize treated with DCPD-PolyP at full concentration (C1) exhibited 170 % higher root biomass (12.783 g), 240 % greater shoot biomass (29.090 g), and 42 % increased plant height (136.83 cm) compared to controls, outperforming traditional triple superphosphate (TSP) and unmodified DCPD. Notably, P uptake surged by 280 % (5.434 g at C1), with phosphorus use efficiency peaking at 56.93 under reduced doses. Soil Olsen-P levels reached 61.930 mg kg−1 (C2), significantly exceeding TSP and control treatments. Remarkably, DCPD-PolyP enhanced bioavailability of key micronutrients (Ca, Cu, Mg, Mn, Fe, Zn) in both plants and soil, demonstrating dual benefits for crop nutrition and soil health. These results highlight DCPD-PolyP's potential to revolutionize nutrient management in agriculture, bridging the gap between advanced material science and sustainable food production by optimizing resource efficiency.